Administração penitenciária: o controle da população carcerária a partir da gestão partilhada entre diretores, judiciário e facções - Jesus Filho, José de (2017)
This dissertation provides a critical analysis of contemporary control institutions responsible for the prison population within the state of São Paulo. More specifically, it analyzes the management conflict that characterizes its modus operandi. By focusing on the prison wardens, the research endeavors to understand how the behavior of these actors is influenced by a number of other powers, such as judges, inmates, and the bureaucracy in the state correctional department, to which wardens are subordinate. The research shows that the emergence of these other influences has led to institutional fragmentation in the exercise of power over the prison population. To this end, the research carries out a detailed characterization of these powers and subsequently analyzes the interactions between these actors including their tensions and cooperations over the years. The prominent actors included in analysis are the prison central administration, the warden deputy, the security warden, prison gangs, judges, public defenders and the media. By conducting a critical analysis of the principles that guide the behavior of these actors, the dissertation is able to identify the characteristics of the profound crisis that defines prison administration in São Paulo in the last decades.